2015
DOI: 10.5888/pcd12.140532
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Factors Related to Boys’ and Girls’ Park-Based Physical Activity

Abstract: IntroductionParks provide opportunities for physical activity for children. This study examined sex differences in correlates of park-based physical activity because differences may indicate that a standard environmental intervention to increase activity among children may not equally benefit boys and girls.MethodsThe System for Observation Play and Recreation in Communities was used to measure physical activity among 2,712 children and adolescents in 20 neighborhood parks in Durham, North Carolina, in 2007. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…A study examining park use found that the positive association between park programming (e.g. social activities) and girls’ PA was stronger when there were more recreational facilities available, 20 lending support to the hypothesis that PA resource availability may strengthen social influences on PA. Adolescents with greater friend support and more-positive attitudes may be more aware of and use nearby PA resources more frequently.…”
Section: Discussionmentioning
confidence: 86%
“…A study examining park use found that the positive association between park programming (e.g. social activities) and girls’ PA was stronger when there were more recreational facilities available, 20 lending support to the hypothesis that PA resource availability may strengthen social influences on PA. Adolescents with greater friend support and more-positive attitudes may be more aware of and use nearby PA resources more frequently.…”
Section: Discussionmentioning
confidence: 86%
“…It is also necessary to offer recreational areas that respond to the demand according to the age of the users [57][58][59][60]. Not all citizens are interested in the same spaces and activities and that is why it is not enough to build the park.…”
Section: Discussionmentioning
confidence: 99%
“…The number of recreational facilities in combination with formal activities is positively associated with girls' activity. However, a significant interaction with young children (0-5 years of age) and the presence of parents are negatively associated with PA in parks [59].…”
Section: Opportunities Of Physical Activity With Cognitive Load Offermentioning
confidence: 92%
“…Although parks and related environmental factors have been shown to increase children's PA, few studies include analyses for specific race/ethnic subgroups in lowerincome communities. 46,47 Evidence is limited on the key programmatic, social, and environmental features of parks that encourage PA. To benefit children from lower-income and racial and ethnic minority populations, such evidence is needed to guide park programming, design, planning, and resource allocations.…”
Section: Out-of-school Time: Youth Pa In Summer: Patterns and Disparimentioning
confidence: 99%